The Influence of Organizational Culture and Work Motivation on Employee Performance with Job Satisfaction as a Mediation Variable at PT. Bengkulu Kokoh Perkasa - Rachmad, Rachmad Julius Fikri; Hartono, Arif (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2024)
This research aims to analyze the influence of organizational culture and work motivation on employee performance with job satisfaction as an intervening variable. This research was conducted at PT Bengkulu Kokoh Perkasa, with a population of 64 employees, namely all employees and 64 respondents. This data was collected using a 1-6 Likert Scale questionnaire. Data analysis used the SEM-PLS quantitative method with the help of PLS 4.0 software. Based on the test results and data analysis of this research, it was found that 1) organizational culture has a positive and significant effect on employee performance, 2) work motivation has a negative and insignificant effect on employee performance, 3) organizational culture has a positive and significant effect on job satisfaction, 4) work motivation has a positive and significant effect on job satisfaction, 5) job satisfaction has a positive and significant effect on employee performance, 6) job satisfaction can mediate the relationship between organizational culture and employee performance, 7) job satisfaction can mediate work motivation on employee performance.